Комплексная математическая модель управления рисками металлургического предприятия (Путеводитель предпринимателя, 2020)
Necessity of use of complex models of management by risks in metallurgy is proved. The mathematical model including all stages of managerial process by risks of the metallurgical enterprise is offered.